PENINGKATAN PENGELOLAAN BUDIDAYA KARANG HIAS LESTARI BERBASIS MASYARAKAT - Kasmi, Mauli; Asriany, Asriany; Makkulawu, Andi Ridwan; Usman, Arif Fuddin (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2020)
The coral potential has Indonesia the first-class exporter of nature coral. The paradigm of the export market of corals is very interested in cultivated corals products because of the diversification of production, so that the variety can meet the export market as an opportunity to conduct business activities that can improve the welfare of the fishing community, regional income and national income. The purpose of this program is to obtain a number of products, types and quality as well as an increase in the quality of coral habitats in general in a planned manner that can guarantee the sustainability of ornamental coral businesses that can stimulate the nuances of business competition full of creativity and dedication with a touch of innovation efforts to continuously develop production without dependence on the product natural. The method used is fragmentation where the colony is taken from a particular parent colony by planting an artificial substrate paste placed on the construction and design of an environmentally friendly table rack at sea that can form coral or coral buds that produce the number and quality of export standards from the production plan of the yield Ornamental coral cultivation in a sustainable and community-based manner. Production results before being developed and subsequently sold to the market must first go through the process of applicable regulations. The technology developed is eco-technology (ecosystem technology) which is certainly oriented towards agribusiness through a seafarming program (coral cultivation) or an effort to utilize sustainable management methods (suistainable) based on community and tourism. The improvement of ornamental corals product quality is innovative product diversification in the inventory system with the application of ammonia (protein skimmer) removal equipment for ornamental corals at harvest time and maintained in an aquarium before being exported.